Polymers and Their Application in 3D Printing (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Dear Colleagues, Fused filament fabrication, also known as 3D printing, is extensively used to produce prototypes for applications in, e.g., the aerospace, medical, and automotive industries. In this process, a thermoplastic polymer is fed into a liquefier that extrudes a filament while moving in successive X–Y planes along the Z direction to fabricate a 3D part in a layer-by-layer process. Due to the progressive advances of this process in industry, the application of polymeric (or even composite) materials have received much attention. Researchers and industries now engage in 3D printing by implementing numerous polymeric materials in their domain. In this Special Issue, we will present a collection of recent and novel works regarding the application of polymers in 3D printing.